Women in higher education: predictors and implications - Mohd. Noor, Noraini (IIUM Press and IPPTN, 2009)
Introduction: This chapter addresses women's increased participation in higher education in Malaysia, focusing on the social, cultural and psychological factors that have made this possible. To understand the present education system in Malaysia, a brief history of the country is first presented.